Analysis of the Utilization of LearningApps Media on the Understanding Ability of 2nd Grade Elementary Students on Pancasila Education Material “Symbols of Religious Diversity in Indonesia” - Az Zahra, Khoirina (JPG: Jurnal Pendidikan Guru, 2025)
This study aims to analyze the use of interactive learning media LearningApps on the ability of 2nd grade elementary school students to understand the Pancasila education material on the symbols of religious diversity in Indonesia. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the use of LearningApps significantly influences students' ability to understand the aspects of Bloom's taxonomy at levels C1 to C4, including the ability to remember, understand, apply, and analyze. This media encourages active participation, improves memory, strengthens learning concepts, and fosters an attitude of tolerance and mutual cooperation. The role of teachers is very important in facilitating the transition process from conventional to digital learning. LearningApps has been proven to be an interactive learning media that is in accordance with the characteristics of students at the elementary education level in the digital era.